2020
DOI: 10.1029/2020jd033446
|View full text |Cite
|
Sign up to set email alerts
|

Land Surface Temperature Trend and Its Drivers in East Africa

Abstract: Land surface temperature (LST) is affected by surface-atmosphere interaction. Yet, the degree to which surface and atmospheric factors impact the magnitude of LST trend is not well established. Here, we used surface energy balance, boosted regression tree model, and satellite observation and reanalysis data to unravel the effects of surface factors (albedo, sensible heat, latent heat, and ground heat) as well as incoming radiation (shortwave and longwave) on LST trends in East Africa (EA). Our result showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 63 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…Over regions of strong coupling in the Sahel and Eastern Africa, land-atmosphere coupling has been linked with the increase in surface temperatures during anomalously low SM events at sub-seasonal to seasonal timescales (Talib et al 2022;Abera et al 2020). This is related to SM controlling the partitioning of latent and sensible heat flux in transitional zones (Gallego-Elvira et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over regions of strong coupling in the Sahel and Eastern Africa, land-atmosphere coupling has been linked with the increase in surface temperatures during anomalously low SM events at sub-seasonal to seasonal timescales (Talib et al 2022;Abera et al 2020). This is related to SM controlling the partitioning of latent and sensible heat flux in transitional zones (Gallego-Elvira et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of soil moisture anomalies has been demonstrated to influence local to regional climate beyond planetary boundary layer (PBL) variables. Over East Africa, Abera et al (2020) noted that land surface characteristics such as leaf area index and soil moisture control about 47% of the temporal variability of surface temperatures. Moreover, Dirmeyer et al (2009) reported that soil moisture memory persisted for up to about 40 days in Southern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also been conducted finding relationships of temperature trends with wind firms [73]- [75], earthquake impact [76], CO2 emission [77], and vector borne diseases [78]. Driving factors or causes of warming or cooling trends were also studied [19,33,46,49,[79][80][81]. Most of these studies were conducted using MODIS LST data with a spatial resolution of 1 km, and a few with 5.6 km.…”
Section: A Modismentioning
confidence: 99%
“…Figure 1 provides an overview of the application fields of LST. LST has been used to study global warming [3][4][5][6][7][8][9][10][11][12][13][14][15][16], interannual climate variabilities [5,[7][8][9][10]14,17], heat waves [18][19][20], droughts [21][22][23][24][25], soil moisture dynamics [22,23,[26][27][28][29], forest dynamics [28,[30][31][32][33][34][35][36][37][38][39], general vegetation-temperature interactions [15,20,[24]…”
Section: Introduction 1relevance Of Satellite-derived Lstmentioning
confidence: 99%